RESPON BIBIT KAKAO PADA BAGIAN PANGKAL, TENGAH DAN PUCUK TERHADAP PEMUPUKAN MAJEMUK - - Sutardi; Reki Hendrata (Universitas Trunojoyo Madura, 2009)
The research was conducted in Paingan, Maguwoharjo, Depok Subdistrict, Sleman Regency from May until August 2005. The objective of the studies are (1) to know respon of growth of seed of kakao part of jetty, middle and sprout to spraying fertilizer compon (2) to determine situation of seed in fruit, (3) to also the concentration fertilizermost precise compon for growth of seed kakao plant. The research used methode field observation was arranged in a factorial completely ramdomized design (RAL) with two factor. Namely first factor of seed situation (L) consisted of by 3 level, that (L1) part of fruit jetty, (L2) middle shares of fruit, and (L3) top shares of fruit and second factor concentration Wuxal fertilize that ( K), consisted of 4 level (K0) : 0% (without Wuxal fertileze), (K1) : 0,2% (2 ml fertilizer1000 ml weter), K2 : 0,4% ( 2 ml fertilizer/ 500 ml weter), K3 : 0,6% (2 ml fertilizer 333,34 ml weter), obtained 12 treatment combination, every treatment combination repeated with 3, each treatment consisted by 5 seed. The observation conducted were cover high crop, sum up leaf and length grow on. The results showed that indicate best seed growth in middle shares fruit. An centration compon fertilize giving best influence 0,35%,between situation of seed in fruit with concentration fertilizer compon of thuse no interaction in influencing growth of seed kakao plant.